Acenaphthene adsorption onto ultrasonic assisted fatty acid mediated porous activated carbon-characterization, isotherm and kinetic studies. (December 2021) - Kumar, J. Aravind; Kumar, P. Senthil; Krithiga, T.; Prabu, D.; Amarnath, D. Joshua; Sathish, S.; Venkatesan, D.; Hosseini-Bandegharaei, Ahmad; Prashant, P.
Abstract: Adsorbents originated from biological materials play a vital role in the remediation of diverse toxic pollutants due to their high efficacy, low cost and being environmentally friendly. The present study focusses on the palm shell activated carbon obtained from agricultural waste precursor (palm shell) with the aid of oleic acid activation along with ultrasonic assistance and its effective utilization for acenaphthene adsorption from aqueous and real effluent. The synthesized Ultrasonic assisted palm shell activated carbon (UAC) possessed high surface area of 506.84 m 2 /g and distinct porous structure as depicted by SEM analysis. The outcomes of zero discharge analyses and acenaphthene adsorption results vouchsafed that, using oleic acid as an effective catalyst, is explicitly advantageous to combine with ultrasonic assistance to fabricate a highly efficient adsorbent for acenaphthene removal from aqueous solution. The UAC obtained at the selected parameters levels, such as temperature of 45 °C and ultrasonic time of 40 min, has the adsorption capacity of 52.745 mg/g. Sips isotherm model computed from the experimental data gave the best fit among the examined isotherm models. To complete the study of adsorption properties of UAC towards acenaphthene, kinetic modeling and thermodynamic aspects of the adsorption process were also scrutinized. The kinetic studies proved that pseudo-second order model is compatible with the experimental data and thermodynamic results revealed that the adsorption process is of endothermic nature. Overall, ultrasonic-assisted preparation of activated carbon from palm shell actuated using Oleic acid was found to be a highly efficient adsorbent which was suitable for acenaphthene removal from aqueous solution. Graphical abstract: Image 1 Highlights: Acenaphthene removal was made using ultrasonic assisted oleic acid mediated porous activated carbon. Oleic acid, precursor combined with ultrasonic activation enhanced acenaphthene adsorption. Regression application of non-linear kinetic mechanism was tested. Sips isotherm was well fitted to equilibrium estimation. Thermodynamic studies was evaluated using Sips constant.